(untitled) (Editora Impacto Científico, 2025)
Body image, which comprises positive and negative perceptions of one’s body, is a multifaceted construct. While traditional research has primarily delved into the negative dimensions associated with eating disorders, recent academic efforts have shifted toward understanding the concept of positive body image. This encompasses aspects such as body appreciation and acceptance, as well as embracing broader beauty ideals. Recent investigations have placed an emphasis on exploring predictors and interventions aimed at nurturing a positive body image, particularly among young adult and college women, who are considered vulnerable to developing eating disorders. This highlights the critical need for systematic review studies to comprehensively examine existing theoretical frameworks in this area. The present study adopts a qualitative, exploratory and descriptive approach within the scope of the systematic literature review methodology. The review protocol was initially registered with PROSPERO and PRISMA guidelines were adopted. The databases PubMed, Scopus, Embase, Web of Science and PsycInfo were used to identify original articles that evaluated theoretical models of positive body image specifically in young adult women. The objective was to conduct a systematic review in order to synthesize the theoretical support on positive body image available to young university women. The systematic review yielded a total of 12 studies that met the inclusion criteria. Among the theoretical models identified, the Intuitive Eating Acceptance Model emerged as the most widely supported model in the literature. Variables explored in the context of positive body image models encompassed body appreciation, self-compassion, self-esteem, exercise motivation, intuitive eating, resilience, self-objectification, acceptance of others, family support, social comparison, body mass index, and media influence. Although the Intuitive Eating Acceptance Model demonstrates robust theoretical support, the review identified limitations related to temporal constraints and and lack of sampling diversity that warrant further investigation.